Composite conductive structure, preparation method and photovoltaic cell
By adopting a composite conductive structure in the TOPCon battery, including a thinner silver-based conductive material and a first conductive layer of glass material, and a second conductive layer of base metal conductive material, the problem of high silver usage due to large front gate thickness is solved, and the effect of reducing production costs and improving current conduction efficiency is achieved.
Patent Information
- Application Number
- CN202411811236.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-15
AI Technical Summary
In TOPCon battery technology, when the thickness of the front gate is 5 μm to 9 μm, more slurry is used, resulting in a larger amount of silver used and increasing production costs.
A composite conductive structure is adopted, including forming a first conductive layer on the substrate, with a thickness of 1 μm to 2 μm, the material includes a silver-based conductive material, a glass material and an inorganic additive, and a second conductive layer is formed on the first conductive layer, and a base metal conductive material is used.
By reducing the thickness and silver content of the first conductive layer, the production cost is reduced, while using the second conductive layer of the base metal conductive material reduces the lateral resistance and improves the current conduction efficiency.
Smart Images

Figure CN119836056A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of photovoltaic cell manufacturing, and in particular to a composite conductive structure and a preparation method thereof, and a photovoltaic cell. Background Art
[0002] TOPCon (Tunnel Oxide Passivated Contact) battery technology is becoming more and more mature and is increasingly favored by people and the market. In related technologies, when TOPCon batteries use laser-assisted sintering to form a grid on the front of the battery, the thickness of the front grid is generally sintered to 5μm to 9μm. The sufficient thickness can ensure that the silver paste forms a continuous and dense conductive path after sintering.
[0003] However, when the thickness of the front grid is 5 μm to 9 μm, more paste is used, and the amount of silver used in the paste is large, which is not conducive to cost saving. Summary of the invention
[0004] In view of this, the embodiments of the present disclosure provide a composite conductive structure and a preparation method and a photovoltaic cell to solve the problems existing in the related art.
[0005] According to a first aspect of the embodiments of the present disclosure, a composite conductive structure is provided, comprising:
[0006] substrate;
[0007] A first conductive layer is formed on the substrate, wherein the thickness of the first conductive layer is 1 μm to 2 μm, and the material of the first conductive layer includes a silver-based conductive material, a glass material, and an inorganic additive;
[0008] and a second conductive layer formed on the first conductive layer, the second conductive layer having a conductive material including a base metal conductive material.
[0009] A second aspect of the embodiments of the present disclosure provides a method for preparing a composite conductive structure, comprising:
[0010] providing a substrate;
[0011] Forming a first conductive layer on the substrate using a first conductive paste, wherein the thickness of the first conductive layer is 1 μm to 2 μm;
[0012] A second conductive layer is formed on the first conductive layer using a second conductive paste, wherein the conductive material of the second conductive layer includes a base metal conductive material.
[0013] A third aspect of the embodiments of the present disclosure provides a photovoltaic cell comprising the composite conductive structure of the first aspect of the embodiments of the present disclosure.
[0014] In one or more technical solutions provided in the embodiments of the present disclosure, a first conductive layer is formed on a substrate using a first conductive paste, and the thickness of the first conductive layer is 1 μm to 2 μm. Therefore, compared with sintering the grid line thickness on the front of the battery to 5 μm to 9 μm using a conductive paste, the thickness of the first conductive layer in the embodiments of the present disclosure is significantly reduced, which means that the volume of the first conductive layer is reduced under the same area. At this time, since the material of the first conductive layer includes a silver-based conductive material, a glass material, and an inorganic additive, when a thinner first conductive layer is formed, the silver content in the first conductive layer can be reduced, thereby reducing production costs.
[0015] On this basis, in order to avoid the problem of high lateral resistance caused by the thin thickness of the first conductive layer, the embodiment of the present disclosure forms a second conductive layer on the first conductive layer, and the conductive material of the second conductive layer includes a base metal conductive material. Therefore, the current of the first conductive layer can be transmitted to the second conductive layer, and the base metal conductive material of the second conductive layer has more free electrons, which can move relatively smoothly in the lateral direction under the action of the electric field, so that the second conductive layer can be used to conduct the current laterally, so that the current no longer relies solely on the thinner and possibly higher resistance first conductive layer when conducting laterally, thereby avoiding the problem of high lateral resistance caused by the thin thickness of the first conductive layer.
[0016] In addition, if the total thickness of the first conductive layer and the second conductive layer is 5 μm to 9 μm, the presence of the base metal conductive material significantly reduces the proportion of silver in the entire conductive structure without changing the overall thickness of the gate line, thereby saving costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings described herein are used to provide a further understanding of the present disclosure and constitute a part of the present disclosure. The illustrative embodiments of the present disclosure and their descriptions are used to explain the present disclosure and do not constitute an improper limitation on the present disclosure. In the drawings:
[0018] Figure 1 is a schematic structural diagram of a composite conductive structure according to an embodiment of the present disclosure;
[0019] Figure 2 A preparation flow chart of a method for preparing a composite conductive structure provided in an embodiment of the present disclosure;
[0020] Figure 3 is a scanning electron microscope cross-sectional view of the first conductive layer of an embodiment of the present disclosure;
[0021] Figure 4 is a viscosity diagram of the first conductive paste under steady-state shearing of an embodiment of the present disclosure;
[0022] Figure 5is a dynamic strain amplitude scanning diagram of the first conductive paste of the embodiment of the present disclosure;
[0023] Fig. 6A This is a scanning electron microscope image of a first conductive paste after laser-assisted sintering according to an embodiment of the present disclosure;
[0025] Figure 6B This is a scanning electron microscope image of another first conductive paste after laser-assisted sintering according to an embodiment of the present disclosure;
[0026] Figure 7 This is an EL emission characteristic diagram of the first conductive paste after laser-assisted sintering of the embodiment of the present disclosure.
[0027] Reference numerals: 110 - substrate, 120 - first conductive layer, 130 - second conductive layer. DETAILED DESCRIPTION
[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are not used to limit the present disclosure.
[0029] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.
[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present disclosure, "multiple" means two or more, unless otherwise clearly and specifically defined. "Several" means one or more, unless otherwise clearly and specifically defined.
[0031] In the description of the present disclosure, it is necessary to understand that the directions or positional relationships indicated by the terms "upper", "lower", "front", "back", "left", "right", etc. are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present disclosure and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present disclosure.
[0032] In the description of the present disclosure, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present disclosure can be understood according to specific circumstances.
[0033] It should be noted that, in the present invention, the words "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the present disclosure should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of <24P09481CN>
[0034] Words such as "exemplary" or "such as" are intended to present related concepts in a concrete manner.
[0035] In the present invention, "at least one" means one or more, and "plurality" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, at least one of a, b or c can mean: a, b, c, the combination of a and b, the combination of a and c, the combination of b and c, or the combination of a, b and c, where a, b, c can be single or multiple.
[0036] As an innovative achievement in the photovoltaic field that has attracted much attention in recent years, TOPCon battery technology is playing an increasingly important role in the context of energy transformation. TOPCon batteries achieve high photoelectric conversion efficiency with their unique tunneling oxide passivation contact structure. In the production process of batteries, laser-assisted sintering technology is widely used to form the gate on the front of the battery. By precisely controlling the sintering process, the thickness of the front gate is sintered to 5μm to 9μm. This thickness range can ensure that the silver paste forms a continuous and dense conductive path after sintering, thereby effectively transmitting current and improving the performance of the battery.
[0037] However, current technology faces some challenges when processing the back grid. When the thickness of the front grid is also 5μm to 9μm, more paste is needed, among which the amount of silver is large. In the current market environment, silver, as a precious metal, has a relatively high price and fluctuates greatly. The large-scale use of silver paste not only increases production costs, but also makes the price of batteries uncompetitive in the market, which has brought certain obstacles to the sustainable development and large-scale promotion and application of the photovoltaic industry.
[0038] In view of the above problems, the embodiments of the present disclosure provide a composite conductive structure and a preparation method and a photovoltaic cell to reduce the amount of silver used in the front grid line of the photovoltaic cell and reduce the cost. The photovoltaic cell includes the composite conductive structure.
[0039] Figure 1 Schematic diagram of the structure of the composite conductive structure provided by the exemplary embodiment of the present disclosure. Figure 1 As shown, the composite conductive structure of the embodiment of the present disclosure includes a substrate 110 and a first conductive layer 120 formed on the substrate 110 . The thickness of the first conductive layer 120 is 1 μm to 2 μm.
[0040] Compared with using conductive paste to sinter the grid line thickness on the front side of the battery to 5μm to 9μm, the thickness of the first conductive layer 120 in the embodiment of the present disclosure is significantly reduced, which means that under the same area, the volume of the first conductive layer 120 is reduced. At this time, since the material of the first conductive layer 120 includes silver-based conductive material, glass material and inorganic additives, when a thinner first conductive layer 120 is formed, the silver content in the first conductive layer 120 can be reduced, thereby reducing production costs.
[0041] It can be understood that the above-mentioned substrate may include an N-type silicon substrate. A very thin tunneling oxide layer (usually silicon dioxide) and a doped polysilicon layer may be formed on the front side of the N-type silicon substrate. These two layers constitute the passivation contact structure of the TOPCon battery, and the front gate line is usually formed by printing a conductive paste (such as silver paste) on this passivation contact structure.
[0042] In one example, the material of the first conductive layer includes a silver-based conductive material, a glass material, and an inorganic additive. It should be understood that the glass material of the embodiment of the present invention can be in a powdered state. Among them, the silver-based conductive material, as a conductive component, provides good conductivity. In the sintering stage, the glass material first plays a role, starts to melt at a lower temperature, and acts as a flux. The molten glass material can wrap the silver-based conductive material, reduce the sintering temperature of the silver-based conductive material, and promote the formation of a continuous conductive path between the silver-based conductive materials. The glass material plays a bonding and filling role between the silver-based conductive materials and between the battery surface, and can fill the gaps between the silver-based conductive materials to enhance the compactness of the grid. The inorganic additive can be physically adsorbed or chemically bonded with the glass material and the silver-based conductive material. For example, the inorganic additive can form a cross-linked structure with certain components in the glass material to enhance the strength of the glass phase. At the same time, for the silver-based conductive material, the inorganic additive can form a protective film on its surface to improve the oxidation resistance and corrosion resistance of the silver-based conductive material. This mutual cooperation enables the formed gate structure to remain stable during long-term use and effectively transmit current even under harsh environmental conditions such as high temperature, high humidity, ultraviolet radiation, etc.
[0043] For the silver-based conductive material, it can be any one or two of silver powder, Ag-M alloy powder, and Ag-Cu-N alloy powder, wherein M includes one or more of Al, Au, Ba, Bi, Ca, Cd, Ce, Co, Cr, Cu, Dy, Er, Eu, Fe, Ga, Gd, Ge, Ho, In, Ir, La, Lu, Mg, Mn, Mo, Nd, Ni, Pb, Pd, Pm, Pr, Pt, Re, Rh, Ru, Sb, Sc, Si, Sm, Sn, Sr, Tb, Te, Ti, Tm, Y, Yb, Zn, and Zr; and N includes one or more of P, Zn, Ni, Pb, and Sn.
[0044] For example, Figure 1 As shown, the composite conductive structure of the embodiment of the present disclosure further includes a second conductive layer 130 formed on the first conductive layer 120 , and the conductive material of the second conductive layer 130 includes a base metal conductive material.
[0045] In the embodiment of the present disclosure, the second conductive layer 130 is formed on the first conductive layer 120, so that the current of the first conductive layer 120 can be transmitted to the second conductive layer 130. The base metal conductive material of the second conductive layer 130 has a large number of free electrons. These free electrons can move relatively smoothly in the lateral direction under the action of the electric field, so that the second conductive layer 130 can be used to conduct the current laterally, so that the current no longer relies solely on the thinner and possibly higher resistance first conductive layer 120 during lateral conduction, thereby avoiding <24P09481CN>
[0046] The problem of high lateral resistance is caused by the thin thickness of the first conductive layer 120 .
[0047] On this basis, if the total thickness of the first conductive layer 120 and the second conductive layer 130 is 5 μm to 9 μm, the presence of the base metal conductive material significantly reduces the proportion of silver in the entire conductive structure without changing the overall thickness of the gate line, thereby saving costs.
[0048] Exemplarily, the above-mentioned base metal conductive material includes at least one of copper-based conductive material, aluminum-based conductive material, nickel-based conductive material and zinc-based conductive material. The copper-based conductive material includes at least one of copper and copper alloy, the aluminum-based conductive material includes at least one of aluminum and aluminum alloy, the nickel-based conductive material includes at least one of nickel and nickel alloy, and the zinc-based conductive material includes at least one of zinc and zinc alloy.
[0049] In one achievable manner, in the first conductive layer 120 of the embodiment of the present disclosure, the mass ratio of the silver-based conductive material, the glass material and the inorganic additive is (70-85): (3-10): (0.1-2). In this mass ratio, the silver-based conductive material is dominant, which can ensure good conductivity, form a better conductive path, and reduce energy loss during current transmission. The glass material can be effectively melted at the sintering temperature, which plays a role in reducing the sintering temperature of the silver-based conductive material. It can also fully assist the melting of the silver-based conductive material, so that the silver-based conductive material is sintered more completely, and will not form too much glass phase to cover the silver-based conductive material after sintering, affecting the conductive performance. At the same time, the inorganic additive at this ratio can ensure that the silver-based conductive material is sintered in a suitable chemical environment to avoid problems such as oxidation and agglomeration. If the proportion of inorganic additives is too high, too many impurities may be introduced to interfere with the sintering process. If the proportion is too low, the sintering process cannot be effectively adjusted, affecting the quality of the gate.
[0050] In one achievable manner, in the first conductive layer 120 of the embodiment of the present disclosure, the particle size parameters D50 of the silver-based conductive material, the glass material and the inorganic additive are all less than or equal to 1.5 μm, and D100 are all less than 3 μm.
[0051] In practical applications, since the thickness of the first conductive layer 120 is 1 μm to 2 μm, the particle size parameters D50 of the silver-based conductive material, glass material and inorganic additive are set to be less than or equal to 1.5 μm, and D100 is less than 3 μm, which can ensure that the material particles will not occupy a large volume due to excessive particle size. Therefore, a smaller particle size can improve the distribution uniformity and contact effect of the glass, and at the same time avoid the possibility of ups and downs of the first conductive layer 120 caused by large particles, which is unfavorable to the lateral charge transmission. Moreover, the parameter restrictions of D50 and D100 can make the silver-based conductive material, glass material and inorganic additive material better filled during the deposition or coating process, ensuring the compactness of the first conductive layer. For example, in screen printing or other coating processes, materials with suitable particle sizes can be more evenly distributed on the substrate to form a conductive layer with stable quality. This uniform conductive layer can collect and transmit current more effectively, reduce the situation where the local current is too large or too small, and thus improve the photoelectric conversion efficiency of the battery.
[0052] In one achievable manner, in the first conductive layer 120 of the embodiment of the present disclosure, the glass material includes a first glass material, a second glass material and a third glass material, the glass transition temperature of the first glass material is less than or equal to 400°C, the glass transition temperature of the second glass material is greater than 400°C, and the glass transition temperature of the third glass material is 400°C to 450°C.
[0053] In practical applications, by selecting three glass materials with different glass transition temperatures, the particle contact and fusion of the silver-based conductive material can be optimized and melted in sequence. This melting sequence at different temperatures can form a temperature gradient, which helps to gradually optimize the structure of the first conductive layer during the entire sintering process. Among them, the first glass material plays a bonding role in the early stage, the second glass material plays a filling role in the middle and late stages, and the third glass material plays a transition and synergistic role, which together enable the silver-based conductive material to form a more continuous and uniform conductive path, thereby reducing the resistance of the conductive layer and improving the photoelectric conversion efficiency of the battery.
[0054] For example: First, at the beginning of the sintering process, when the temperature gradually rises and reaches the transition temperature of the first glass material, the first glass material first softens and melts. This helps to promote the fusion of the particles of the silver-based conductive material at a lower temperature stage, laying the foundation for the subsequent formation of a continuous conductive path. At the same time, the first glass material can be used as an initial binder to initially fix the silver-based conductive material and the inorganic additive together to prevent the displacement of the materials during the subsequent heating process. Secondly, when the temperature rises above the transition temperature of the second glass material, the second glass material begins to melt and further mixes with the silver-based conductive material and the first glass material that have been initially fused. The second glass material can fill the gaps that may exist between the first glass material and the silver-based conductive material, further enhancing the compactness of the conductive layer. The third glass material in the intermediate temperature range plays a transition and balancing role in the sintering process, and plays a role in the temperature range where the first glass material has begun to soften but the second glass material has not yet melted, and can adjust the viscosity and fluidity of the entire glass system. In this temperature range, the third glass material can work together with the first glass material to better wrap the silver-based conductive material, while preparing for the subsequent melting and filling of the second glass material, making the formation process of the conductive layer smoother and more continuous.
[0055] Exemplarily, the mass ratio of the first glass material, the second glass material and the third glass material is (10-50):(20-50):(0-80), preferably (10-20):(30-40):(30-60).
[0056] In an optional manner, in the first conductive layer 120 of the embodiment of the present disclosure, the first glass material, the second glass material and the third glass material all include SiO2, B2O3, Al2O3, PbO, ZnO, Bi2O3, alkali metal oxides and alkaline earth metal oxides. In the first glass material, the ratio of the sum of the molar number of cations of PbO, ZnO, Bi2O3, alkaline earth metal oxides and alkali metal oxides to the total molar number of cations of the first glass material is greater than 40%, and in the second glass material, the ratio of the sum of the molar number of cations of PbO, ZnO, Bi2O3, alkaline earth metal oxides and alkali metal oxides to the total molar number of cations of the second glass material is less than or equal to 20%. In the third glass material, the ratio of the sum of the molar number of cations of PbO, ZnO, Bi2O3, alkaline earth metal oxides and alkali metal oxides to the total molar number of cations of the third glass material is less than or equal to 40%.
[0057] The disclosed embodiment limits the molar number of cations of PbO, ZnO, Bi2O3, alkali metal oxides and alkaline earth metal oxides in the first glass material, the second glass material and the third glass material. Among them, PbO, ZnO, Bi2O3, alkali metal oxides and alkaline earth metal oxides usually reduce the glass transition temperature, and glass formers such as SiO2, B2O3, Al2O3 increase the glass transition temperature. Therefore, on the basis of limiting the molar number of cations, the transition temperatures of the first, third and second types of glasses will increase in sequence.
[0058] On this basis, by limiting the molar number of cations in the three glass materials, the glass materials can play the best role in different stages of the sintering process, thereby optimizing the particle arrangement and connection of the silver-based conductive material. The first glass material mainly provides a passivation layer such as SiNx and Al2O3 layer for corroding the surface of the silicon wafer. The second glass material has weaker corrosiveness and can further supplement the corrosion effect of the first glass. The third glass mainly limits corrosion and provides better sintering between silver powders.
[0059] In one example, in the first conductive layer 120 implemented in the present disclosure, the inorganic auxiliary agent includes at least one of aluminum oxide, silicon powder, silicon oxide, titanium oxide, boron oxide, silicon boride, and silicon nitride.
[0060] Figure 2 The preparation flow chart of the preparation method of the composite conductive structure provided by the embodiment of the present disclosure is shown as follows: Figure 2 As shown, the present disclosure also provides a method for preparing the composite conductive structure, comprising:
[0061] Step 201: Provide a substrate.
[0062] Step 202: Form a first conductive layer on the substrate using a first conductive paste, wherein the thickness of the first conductive layer is 1 μm to 2 μm.
[0063] For example, the first conductive paste can be printed on the substrate by screen printing or other printing methods such as laser transfer, and the deposition thickness of the first conductive paste is less than or equal to 4 μm, and the thickness after sintering is less than or equal to 2 μm. The sintering process of the first conductive paste on the substrate can include a laser-assisted sintering process or other feasible sintering processes. Therefore, the dielectric layer on the substrate can be finally etched by the first layer of paste combined with the laser-assisted sintering process to achieve ohmic contact.
[0064] Compared with sintering the grid line thickness of the front side of the battery to 5μm to 9μm by using conductive paste, the thickness of the first conductive layer in the embodiment of the present disclosure is significantly reduced, which means that under the same area, the volume of the first conductive layer is reduced. At this time, since the material of the first conductive layer includes silver-based conductive material, glass material and inorganic additive, when forming a thinner first conductive layer, the silver content in the first conductive layer can be reduced, thereby reducing <24P09481CN>
[0065] Production costs.
[0066] Figure 3 A scanning electron microscope cross-sectional view of the first conductive layer of an embodiment of the present disclosure is shown. Figure 3 As shown, the thickness of the first conductive layer is 1 μm to 2 μm.
[0067] Step 203: forming a second conductive layer on the first conductive layer using a second conductive paste, wherein the conductive material of the second conductive layer includes a base metal conductive material.
[0068] The embodiment of the present disclosure forms a second conductive layer on the first conductive layer, and the current of the first conductive layer can be transmitted to the second conductive layer. The base metal conductive material of the second conductive layer has a large number of free electrons. These free electrons can move relatively smoothly in the lateral direction under the action of the electric field. The second conductive layer can be used to conduct the current laterally, so that the current no longer relies solely on the thinner and possibly higher-resistance first conductive layer during lateral conduction, thereby avoiding the problem of high lateral resistance caused by the thin thickness of the first conductive layer.
[0069] For example, the second conductive paste may be printed on the first conductive layer by screen printing or other printing methods such as laser transfer. The sintering process of the second conductive paste on the first conductive layer may include a laser-assisted sintering process, a low-temperature paste curing process to achieve densification, or a high-temperature sintering paste may be sintered in a protective atmosphere to achieve densification, and the protective atmosphere may be nitrogen or a nitrogen-hydrogen mixture.
[0070] In one example, the second conductive paste may include a base metal material, a glass material, and an organic vehicle. The base metal material may include at least one of a copper-based conductive material, an aluminum-based conductive material, a nickel-based conductive material, a zinc-based conductive material, and a silver-clad copper material. The copper-based conductive material includes at least one of copper and a copper alloy, the aluminum-based conductive material includes at least one of aluminum and an aluminum alloy, the nickel-based conductive material includes at least one of nickel and a nickel alloy, and the zinc-based conductive material includes at least one of zinc and a zinc alloy.
[0071] In one example, the first conductive paste may be printed by high temperature sintering to form a first conductive layer on the substrate surface, and then the first conductive layer may be laser assisted sintering to achieve better ohmic contact. The first conductive paste may also be printed by high temperature sintering to form a first conductive layer on the substrate surface, and then the second conductive paste may be printed on the first conductive layer to form a second conductive layer, and then laser assisted sintering may be performed to achieve better ohmic contact.
[0072] For example, when the above-mentioned base metal material is a silver-clad copper material, the first conductive paste can be sintered by a laser-assisted sintering process, and the second conductive layer can be formed on the first conductive layer by a low-temperature curing method. When the above-mentioned base metal material is a copper-based conductive material, an aluminum-based conductive material, a nickel-based conductive material or a zinc-based conductive material, the first conductive paste is first printed by high-temperature sintering to form a first conductive layer on the surface of the substrate, and then the second conductive paste is printed on the first conductive layer, and the second conductive paste is sintered by a laser-assisted sintering process. It should be understood that whether the laser sintering process is used after the formation of the first conductive layer or the second conductive layer, it is to achieve good ohmic contact.
[0073] In one example, before the first conductive paste is used to form the first conductive layer on the substrate in the embodiment of the present disclosure, the preparation method further includes: mixing a silver-based conductive material, a glass material, an inorganic auxiliary agent and an organic carrier to obtain the first conductive paste.
[0074] For example: pre-mix the silver-based conductive material, glass material and inorganic additive, then add them into the organic carrier and stir for 2 to 4 hours, then roll the stirred raw materials on a three-roll mill for 6 to 10 times to further disperse and homogenize, and when the scraper fineness is less than 5 μm, filter with a 400-mesh filter cloth to obtain the first conductive slurry.
[0075] In an alternative approach, Figure 4 A viscosity graph under steady-state shear of the first conductive paste according to an embodiment of the present disclosure is shown. Figure 5 FIG. 4 shows the dynamic strain amplitude scan of the first conductive paste of the embodiment of the present disclosure. Figure 4 and Figure 5 As shown, the rheological characteristics of the first conductive paste of the embodiment of the present disclosure are: under the test of the Anton Paar rheometer, the shear viscosity at a shear rate of 1 / s and a duration of 30 seconds is 50 Pa . s~500Pa . s. Under the oscillating shear condition after the constant shear rate test of 1 / s, the amplitude scan is performed at a frequency of 6.28 radians per second. When the shear strain is 0.1%, the storage modulus value is less than or equal to 10000Pa and greater than 100Pa. The intersection of the storage modulus and loss modulus curves appears in the strain range of 10% to 100%.
[0076] In one example, Fig. 6A A scanning electron microscope image of a first conductive paste after laser-assisted sintering according to an embodiment of the present disclosure is shown. Figure 6B FIG. 2 shows a scanning electron microscope image of another first conductive paste after laser-assisted sintering of an embodiment of the present disclosure. Figure 6A to Figure 6B As shown, the above-mentioned first conductive paste is laser sintered, and after hydrofluoric acid corrosion, the diagonal length of the opening in the scanning electron microscope image is 300-800nm, preferably 300-420nm. It should be understood that the diagonal length of the opening can be understood as the length of the diagonal when the opening shape is a polygon (usually approximately a rectangle or a rhombus). The diagonal length of the opening is 300-800nm, which will not cause the current to pass through due to a small opening, nor will it cause the passivation layer to be damaged due to a large opening, affecting the open circuit voltage, thereby ensuring the effectiveness of the conductive path to a certain extent, which is conducive to maintaining or improving the overall conductive performance.
[0077] The above hydrofluoric acid corrosion conditions include: immersing the silicon wafer in a 5% hydrofluoric acid aqueous solution for 30 seconds at room temperature, maintaining magnetic stirring during the immersion process, and rotating at 600 rpm to maintain a uniform concentration of the hydrofluoric acid aqueous solution; after taking it out, placing it in pure water ultrasound for 10 minutes, and then placing it on a dust-free cloth to absorb moisture.
[0078] For example, Figure 7 FIG. 4 shows the EL emission characteristic diagram of the first conductive paste after laser assisted sintering of the embodiment of the present disclosure. Figure 7 As shown, before the second conductive paste is formed, the inspection is carried out by electroluminescence EL, and the image has the characteristics of uniform distribution of broken gates, and the number of broken gates is greater than 10.
[0079] Exemplarily, the above-mentioned organic carrier includes resin, solvent, surface dispersant and thixotropic agent. For resin, it can include one or more of ethyl cellulose, cellulose acetate butyrate, rosin resin, acrylic resin, and polyvinyl butyral ester. For organic solvent, it can include pine alcohol, butyl carbitol, butyl carbitol acetate, diethylene glycol butyl ether acetate, diethylene glycol dibutyl ether, tripropylene glycol monomethyl ether, diisooctyl adipate, diethylene glycol butyl ether, oleic acid, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, ThixatrolMax, triethylene glycol butyl ether, alcohol fat twelve, alcohol fat sixteen. For surface dispersant, it can include one or more of TDO, ED120, BYK111, and KYC913. As for the thixotropic agent, it may include one or more of alcohol ester 12, terpineol, diethylene glycol butyl ether acetate and diethylene glycol monobutyl ether.
[0080] In an optional manner, the organic carrier may contain, by mass percentage, 1% to 6% of ethyl cellulose, 1% to 40% of polyvinyl butyral, 10% to 70% of diethylene glycol butyl ether acetate, 10% to 60% of tripropylene glycol monomethyl ether, 5% to 50% of diethylene glycol dibutyl ether, 0% to 15% of triethylene glycol diisooctanoate, 3% to 15% of diisooctyl adipate, 0% to 30% of diethylene glycol butyl ether, 0% to 30% of pineneol, 0% to 10% of oleic acid, 0% to 20% of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 0% to 20% of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, 1% to 10% of Thixatrol Max, 0% to 10% hydrogenated castor oil, 0% to 10% TDO, 0% to 10% ED120, 0% to 10% BYK111 and 0% to 10% KYC913.
[0081] As can be seen from the above, the embodiment of the present disclosure uses a first conductive paste to form a first conductive layer on a substrate, and the thickness of the first conductive layer is 1μm to 2μm. Therefore, compared with using a conductive paste to sinter the grid line thickness on the front of the battery to 5μm to 9μm, the thickness of the first conductive layer of the embodiment of the present disclosure is significantly reduced, which means that under the same area, the volume of the first conductive layer is reduced. At this time, since the material of the first conductive layer includes a silver-based conductive material, a glass material, and an inorganic additive, when a thinner first conductive layer is formed, the silver content in the first conductive layer can be reduced, thereby reducing production costs.
[0082] On this basis, in order to avoid the problem of high lateral resistance caused by the thin thickness of the first conductive layer, the embodiment of the present disclosure forms a second conductive layer on the first conductive layer, and the conductive material of the second conductive layer includes a base metal conductive material. Therefore, the current of the first conductive layer can be transmitted to the second conductive layer, and the base metal conductive material of the second conductive layer has more free electrons, which can move relatively smoothly in the lateral direction under the action of the electric field, so that the second conductive layer can be used to conduct the current laterally, so that the current no longer relies solely on the thinner and possibly higher resistance first conductive layer when conducting laterally, thereby avoiding the problem of high lateral resistance caused by the thin thickness of the first conductive layer.
[0083] In order to verify the effect of the composite conductive structure provided by the embodiment of the present disclosure, the embodiment of the present disclosure is demonstrated by comparing the embodiment with a comparative example.
[0084] Embodiment 1
[0085] The method for preparing the composite conductive structure provided in the first embodiment of the present invention comprises the following steps:
[0086] In the first step, a substrate having a tunnel oxide layer and a doped polysilicon layer on the front side is provided.
[0087] The second step is to prepare an organic carrier: 10% of butyl carbitol, 33% of butyl carbitol acetate, 70% of diethylene glycol dibutyl ether, 10% of tripropylene glycol monomethyl ether, and 10% of alcohol lipid twelve are weighed and mixed evenly to obtain a mixed solvent. Then 5% of polyvinyl butyral ester is weighed and added to the mixed solvent, and then 5% of polyamide wax thixotropic agent is added, and then heated to 80°C while stirring. After the resin is completely dissolved, continue stirring for 60 minutes, and then cool to room temperature to obtain an organic carrier.
[0088] The third step is to prepare the first conductive paste: 79.6% of silver powder, 4.5% of glass material, 1.2% of inorganic additives and 14.7% of organic carrier are pre-mixed, and then added into the organic carrier and stirred for 2 hours, and then the stirred raw materials are rolled on a three-roll mill for 6 times to further disperse and homogenize. When the scraper fineness is less than 5μm, filter with a 400-mesh filter cloth to obtain the first conductive paste.
[0089] The glass material includes 50% of the first glass material and 50% of the second glass material. The first glass material includes 40.9% of PbO, 9.1% of ZnO, 13.6% of Bi2O3, 27.3% of B2O3, and 9.1% of SiO2. The second glass material includes 9.7% of PbO, 4.9% of BaO, 2.9% of Bi2O3, 4.9% of ZnO, 29.1% of SiO2, and 48.5% of B2O3. The third glass material includes 30% of PbO, 5% of ZnO, 5% of Bi2O3, 5% of TiO2, 5% of Al2O3, 20% of B2O3, and 20% of SiO2.
[0090] The fourth step is to print a first conductive paste of 3.5 μm to 4 μm on the substrate, and form a first conductive layer of 2 μm after sintering.
[0091] Embodiment 2
[0092] The method for preparing the composite conductive structure provided in the second embodiment of the present invention comprises the following steps:
[0093] In the first step, a substrate having a tunnel oxide layer and a doped polysilicon layer on the front side is provided.
[0094] The second step is to prepare an organic carrier: 10% of butyl carbitol, 33% of butyl carbitol acetate, 70% of diethylene glycol dibutyl ether, 10% of tripropylene glycol monomethyl ether, and 10% of alcohol lipid twelve are weighed and mixed evenly to obtain a mixed solvent. Then 5% of polyvinyl butyral ester is weighed and added to the mixed solvent, and then 5% of polyamide wax thixotropic agent is added, and then heated to 80°C while stirring. After the resin is completely dissolved, continue stirring for 60 minutes, and then cool to room temperature to obtain an organic carrier.
[0095] Step 3: Prepare the first conductive paste: pre-mix 79.6% of silver powder, 4.5% of glass material, 1.2% of inorganic additive and 14.7% of organic vehicle, and then add them into the organic vehicle for stirring.
[0096] After stirring for 2 hours, the stirred raw materials were rolled on a three-roll mill for 6 times to further disperse and homogenize. When the scraper fineness was less than 5 μm, filtration was performed using a 400-mesh filter cloth to obtain a first conductive slurry.
[0097] The glass material includes: 17% of the first glass material, 50% of the second glass material and 33% of the third glass material. The first glass material includes 40.9% of PbO, 9.1% of ZnO, 13.6% of Bi2O3, 27.3% of B2O3 and 9.1% of SiO2. The second glass material includes 9.7% of PbO, 4.9% of BaO, 2.9% of Bi2O3, 4.9% of ZnO, 29.1% of SiO2 and 48.5% of B2O3. The third glass material includes 30% of PbO, 5% of ZnO, 5% of Bi2O3, 5% of TiO2, 5% of Al2O3, 20% of B2O3 and 20% of SiO2.
[0098] The fourth step is to print a first conductive paste of 3.5 μm to 4 μm on the substrate, and form a first conductive layer of 2 μm after sintering.
[0099] Embodiment 3
[0100] The method for preparing the composite conductive structure provided in the third embodiment of the present invention comprises the following steps:
[0101] In the first step, a substrate having a tunnel oxide layer and a doped polysilicon layer on the front side is provided.
[0102] The second step is to prepare an organic carrier: 10% of butyl carbitol, 33% of butyl carbitol acetate, 70% of diethylene glycol dibutyl ether, 10% of tripropylene glycol monomethyl ether, and 10% of alcohol lipid twelve are weighed and mixed evenly to obtain a mixed solvent. Then 5% of polyvinyl butyral ester is weighed and added to the mixed solvent, and then 5% of polyamide wax thixotropic agent is added, and then heated to 80°C while stirring. After the resin is completely dissolved, continue stirring for 60 minutes, and then cool to room temperature to obtain an organic carrier.
[0103] The third step is to prepare the first conductive paste: 79.6% of silver powder, 4.5% of glass material, 1.2% of inorganic additives and 14.7% of organic carrier are pre-mixed, and then added into the organic carrier and stirred for 2 hours, and then the stirred raw materials are rolled on a three-roll mill for 6 times to further disperse and homogenize. When the scraper fineness is less than 5μm, filter with a 400-mesh filter cloth to obtain the first conductive paste.
[0104] Wherein, the glass material includes: 33% of the first glass material, 33% of the second glass material and 34% of the third glass material. The glass material includes 50% of the first glass material and 50% of the second glass material. The first glass material includes 40.9% of PbO, 9.1% of ZnO, 13.6% of Bi2O3, 27.3% of B2O3, and 9.1% of SiO2. The second glass material includes 9.7% of PbO, 4.9% of BaO, 2.9% of Bi2O3, 4.9% of ZnO, 29.1% of SiO2, and 48.5% of B2O3. The third glass material includes 30% of PbO, 5% of ZnO, 5% of Bi2O3, 5% of TiO2, 5% of Al2O3, 20% of B2O3, and 20% of SiO2.
[0105] The fourth step is to print a first conductive paste of 3.5 μm to 4 μm on the substrate, and form a first conductive layer of 2 μm after sintering.
[0106] Comparative Example 1
[0107] Comparative Example 1 of the present invention provides a conductive structure having a substrate and a conductive layer formed on the substrate. The thickness of the conductive layer is 2 μm. The conductive layer is prepared in accordance with the first conductive layer in Example 1 of the present disclosure and does not contain the first glass material in the first conductive paste.
[0108] Comparative Example 2
[0109] Comparative Example 2 of the present invention provides a conductive structure having a substrate and a conductive layer formed on the substrate. The thickness of the conductive layer is 2 μm. The conductive layer is prepared in the same manner as the first conductive layer in Example 1 of the present disclosure, except that it does not contain the second glass material in the first conductive layer.
[0110] Comparative Example 3
[0111] Comparative Example 3 of the present invention provides a conductive structure having a substrate and a conductive layer formed on the substrate. The thickness of the conductive layer is 6 μm, and the preparation method of the conductive layer is consistent with the first conductive layer in Example 1 of the present disclosure.
[0112] Comparative Example 4
[0113] Comparative Example 4 of the present invention provides a conductive structure, which is consistent with the preparation method of the composite conductive structure in Example 1 of the present disclosure, but the glass material of the first conductive layer is a single glass powder, and the single glass powder includes: 40.9% PbO, 9.1% ZnO, 13.6% Bi2O3, and 36.4% SiO2.
[0114] The present disclosure tests the performance of the conductive structures prepared in Examples 1 to 3 and Comparative Examples 1 to 4, and the test results are shown in the following table:
[0115]
[0116]
[0117] As can be seen from the table above, the composite conductive structures prepared in Examples 1 to 3 of the present invention use silver powder and glass materials as the thinner first conductive layer, and use base metal conductive materials as the second conductive layer formed on the first conductive layer. Compared with the comparative example 3 which only uses a 6μm conductive layer, the silver content of the embodiments of the present disclosure is significantly less than that of the comparative example, thus saving costs. Moreover, it can be seen from the data in the table above that the composite conductive structure of the embodiments of the present disclosure improves the contact performance and open circuit voltage while reducing the silver content. It is expected that after the second conductive layer is superimposed, the lateral resistance will be reduced to a level equivalent to that of the comparative example 3.
[0118] On this basis, the conductive structure of comparative example 1 does not contain the first glass material of the present application, and the first conductive layer (silver paste) is also made to be 2 μm thick. It can be seen from the data in the above table that compared with the composite conductive structures of embodiments 1 to 3 of the present disclosure, the contact resistance of comparative example 1 is significantly higher than that of the embodiments of the present disclosure.
[0119] Moreover, the conductive structure of comparative example 2 does not contain the second glass material of the present application, and the first conductive layer (silver paste) is also made to be 2 μm thick. It can be seen from the data in the above table that compared with the composite conductive structures of embodiments 1 to 3 of the present disclosure, the PL relative brightness of the embodiment of the present disclosure is significantly higher than that of comparative example 2, and the corresponding open circuit voltage (voc) is also higher.
[0120] The conductive structure of comparative example 4 adopts a single glass powder. Even though its conductive structure is consistent with the embodiment of the present disclosure, the single glass powder cannot adjust the degree of etching of the substrate, nor can it play a transition and synergistic role like the embodiment of the present disclosure. The PL relative brightness is low, the corresponding Voc is poor, and the contact resistivity is high, which cannot maximize the photoelectric conversion efficiency of the battery.
[0121] It can be seen from the above that the glass materials in the first conductive layer of the composite conductive structure of the embodiment of the present disclosure have a synergistic effect with each other. Therefore, a combination of various features is required to achieve the purpose of the present disclosure.
[0122] The above is only a specific embodiment of the present invention. Obviously, various modifications and combinations can be made thereto without departing from the spirit and scope of the present invention. Accordingly, this specification and the drawings are merely exemplary illustrations of the present invention as defined by the appended claims, and are deemed to have covered any and all modifications, variations, combinations or equivalents within the scope of the present invention. Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is intended to include these changes and variations. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered within the scope of protection of the present invention.
[0123] <24P09481CN>
[0124] Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
[0125] The embodiments of the present disclosure are described above. However, these embodiments are for illustrative purposes only and are not intended to limit the scope of the present disclosure. The scope of the present disclosure is defined by the appended claims and their equivalents. Without departing from the scope of the present disclosure, a person skilled in the art may make a variety of substitutions and modifications, which should all fall within the scope of the present disclosure.
Claims
1. A composite conductive structure, characterized in that: include: substrate; A first conductive layer is formed on the substrate, wherein the thickness of the first conductive layer is 1 μm to 2 μm, and the material of the first conductive layer includes a silver-based conductive material, a glass material, and an inorganic additive; and a second conductive layer formed on the first conductive layer, the second conductive layer having a conductive material including a base metal conductive material.
2. The composite conductive structure according to claim 1, characterized in that: In the first conductive layer, the mass ratio of the silver-based conductive material, the glass material and the inorganic auxiliary agent is (70-85): (3-10): (0.1-2).
3. The composite conductive structure according to claim 2, characterized in that: In the first conductive layer, the particle size parameters D50 of the silver-based conductive material, the glass material and the inorganic additive are all less than or equal to 1.5 μm, and D100 are all less than 3 μm.
4. The composite conductive structure according to claim 2, characterized in that: In the first conductive layer, the glass material includes a first glass material, a second glass material and a third glass material, the glass transition temperature of the first glass material is less than or equal to 400°C, the glass transition temperature of the second glass material is greater than 400°C, and the glass transition temperature of the third glass material is 400°C to 450°C.
5. The composite conductive structure according to claim 4, characterized in that: The first glass material, the second glass material and the third glass material all include SiO2, B2O3, Al2O3, PbO, ZnO, Bi2O3, alkali metal oxides and alkaline earth metal oxides; In the first glass material, the ratio of the sum of the molar numbers of cations of PbO, ZnO, Bi2O3, alkaline earth metal oxides and alkali metal oxides to the total molar number of cations of the first glass material is greater than 40%; in the second glass material, the ratio of the sum of the molar numbers of cations of PbO, ZnO, Bi2O3, alkaline earth metal oxides and alkali metal oxides to the total molar number of cations of the second glass material is less than or equal to 20%; in the third glass material, the ratio of the sum of the molar numbers of cations of PbO, ZnO, Bi2O3, alkaline earth metal oxides and alkali metal oxides to the total molar number of cations of the third glass material is less than or equal to 40%.
6. The composite conductive structure according to claim 2, characterized in that: The inorganic auxiliary agent includes at least one of aluminum oxide, silicon powder, silicon oxide, titanium oxide, boron oxide, silicon boride and silicon nitride.
7. The composite conductive structure according to claim 1, characterized in that: The base metal conductive material includes at least one of a copper-based conductive material, an aluminum-based conductive material, a nickel-based conductive material, and a zinc-based conductive material.
8. A method for preparing a composite conductive structure according to claim 1, characterized in that: include: providing a substrate; Forming a first conductive layer on the substrate using a first conductive paste, wherein the thickness of the first conductive layer is 1 μm to 2 μm; A second conductive layer is formed on the first conductive layer using a second conductive paste, wherein the conductive material of the second conductive layer includes a base metal conductive material.
9. The method for preparing a composite conductive structure according to claim 8, characterized in that: Before forming the first conductive layer on the substrate using the first conductive paste, the method further includes: The silver-based conductive material, the glass material, the inorganic auxiliary agent and the organic carrier are mixed to obtain a first conductive paste.
10. A photovoltaic cell, characterized in that: The photovoltaic cell comprises the composite conductive structure according to any one of claims 1 to 7.
Citation Information
Cited By
Composite conductive structure and preparation method, and photovoltaic cell
WO2026123692A1